α-Synuclein Alters Toll-Like Receptor Expression - Beraud, Dawn; Twomey, Margaret; Bloom, Benjamin; Mittereder, Andrew; Neitzke, Katherine; Ton, Vy; Chasovskikh, Sergey; Mhyre, Timothy R.; Maguire-Zeiss, Kathleen A. (Frontiers in Neuroscience, 2011)
Parkinson’s disease, an age-related neurodegenerative disorder, is characterized by the loss of dopamine neurons in the substantia nigra, the accumulation of α-synuclein in Lewy bodies and neurites, and neuroinflammation. While the exact etiology of sporadic Parkinson’s disease remains elusive, a growing body of evidence suggests that misfolded α-synuclein promotes inflammation and oxidative stress resulting in neurodegeneration. α-Synuclein has been directly linked to microglial activation in vitro and increased numbers of activated microglia have been reported in an α-synuclein overexpressing mouse model prior to neuronal loss. However, the mechanism by which α-synuclein incites microglial activation has not been fully described. Microglial activation is governed in part, by pattern recognition receptors that detect foreign material and additionally recognize changes in homeostatic cellular conditions. Upon proinflammatory pathway initiation, activated microglia contribute to oxidative stress through release of cytokines, nitric oxide, and other reactive oxygen species, which may adversely impact adjacent neurons. Here we show that microglia are directly activated by α-synuclein in a classical activation pathway that includes alterations in the expression of Toll-like receptors. These data suggest that α-synuclein can act as a danger-associated molecular pattern.